Survival of Plodia interpunctella (Hubner), Cadra cautella (Walker), Ephestia kuehniella Zeller, Corcyra cephalonica (Stainton) (Lepidoptera Pyralidae) larvae to starvation (Bollettino di zoologia agraria e bachicoltura, 2024)
The survival skills of Plodia interpunctella, Cadra cautella, Ephestia kuehniella, Corcyra cephalonica larvae have been investigated in laboratory trials. Tests were carried out at three different environmental conditions. C. cephalonica larvae were the most resistant to starvation. Second instar larvae anticipated mould; third instar larvae of the considered species anticipated metamorphosis and in fewcases they became adults.
Keywords: Lepidoptera Pyralidae; larval survival; larval behaviour; starvation; moths of stored products